Agenda 2010 und Hartz IV: Vom rot-grünen Neoliberalismus zum Protest - Heinrich, Michael (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2004)
With the so called Hartz IV law an eminent transformation of german unemployment support is going on. A significant re-distribution from bottom to top, the impoverishment of those who are for a longer time unemployed and because the unemployed are forced to accept any job an important change in the position of the trade unions will take place. As a consequence the Social Democrats loss dramatically support among the voters.